2016
DOI: 10.1186/s12877-016-0371-6
|View full text |Cite
|
Sign up to set email alerts
|

Resource utilisation, costs and clinical outcomes in non-institutionalised patients with Alzheimer’s disease: 18-month UK results from the GERAS observational study

Abstract: BackgroundAlzheimer’s disease (AD), the commonest cause of dementia, represents a significant cost to UK society. This analysis describes resource utilisation, costs and clinical outcomes in non-institutionalised patients with AD in the UK.MethodsThe GERAS prospective observational study assessed societal costs associated with AD for patients and caregivers over 18 months, stratified according to baseline disease severity (mild, moderate, or moderately severe/severe [MS/S]). All patients enrolled had an inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(42 citation statements)
references
References 32 publications
3
39
0
Order By: Relevance
“…Several longitudinal studies have shown that the direct patient costs of AD increase over time or with disease severity [24,25,27,46] and are higher in nursing home residents, compared to communitydwelling patients [26,47]. In community-dwelling patients, the main driver appears to be patient social care costs [24,25], while direct medical costs for patients and for caregivers do not differ according to ADRD severity [24,25,46].…”
Section: Direct Costs Generally Increase Over Time Driven Primarily mentioning
confidence: 99%
See 2 more Smart Citations
“…Several longitudinal studies have shown that the direct patient costs of AD increase over time or with disease severity [24,25,27,46] and are higher in nursing home residents, compared to communitydwelling patients [26,47]. In community-dwelling patients, the main driver appears to be patient social care costs [24,25], while direct medical costs for patients and for caregivers do not differ according to ADRD severity [24,25,46].…”
Section: Direct Costs Generally Increase Over Time Driven Primarily mentioning
confidence: 99%
“…While this is less of a challenge for employed caregivers, where the alternative is paid work, the valuation of time spent by unemployed or retired caregivers is not straightforward and different strategies have been adopted. For example, several studies segregate informal caregivers by employment status, and have reduced the opportunity cost of time for unemployed or retired caregivers to about 25-35% of average labor force wages, commonly referred to as the value of 'leisure time' [23][24][25]58]. In another study, unpaid 'leisure time' in retired carers was valued based on average pension rates [60].…”
Section: Box 2: Indirect Costs-key Takeawaysmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that more men than women participants were recruited and that there were many spousal carers, it is unsurprising that more than two-thirds of carers were females, and this preponderance may have boosted overall unpaid care cost estimates. Numerous studies have reported similar proportions of female carers of people with dementia [8,40].…”
Section: Discussionmentioning
confidence: 99%
“…In Germany, this expenditure was respectively 1,312 €, 2,412 € and 3,722 €, while in the UK it was 1,621 €, 1,836 € and 2,784 €. [30,31]. In Spain, the GERAS II study showed that care for patients with mild dementia is 1,514 € per month, for patients with moderate dementia 2,082 € per month, and increases to 2,818 € in the third stage of the disease.…”
Section: Costs Of Care In Dementiamentioning
confidence: 99%